Collaborative knowledge management portal for managing research at higher learning institution - Abdullah, Rusli; Sahibudin, Shamsul; Alias, Rose Alinda; Selamat, Mohd Hasan (2005)
The role of collaborative technology computing in managing research knowledge is very important and obviously well known. This technology will allow people who are interesting with certain knowledge could be access and share their knowledge among communities of practice at anytime and anywhere regardless of any platform what they have. In this paper, we will discuss the concept and technology of collaborative research management at learning organization in the context of managing knowledge activities as a portal to serve their communities to deposit and disseminate their knowledge at anytime and anywhere. A prototype of KM system is developed that called Collaborative Research Management Portal For Learning Institution or Organization (CoRMPeLO) in order to demonstrated on how the knowledge owned by the communities could be deposit into the system by using knowledge map as well as how this knowledge could be disseminated among them by using agent technology that work as a background and foreground environment. The development of the portal is based on the knowledge management (KM) framework that has been produced from the KM implementation survey and analysis of the related literature. The tool that applied for this KM system development portal is based on the groupware software, which is Lotus Notes.